1.7k views
4 votes
What does x equal? −3(2x−3)=−6x+9

2 Answers

4 votes

Any value of x makes the equation true. All real numbers

Interval Notation: (−∞,∞)

Because if you solve it

-3(2x-3)=-6x+9

distribute

-6x + 9 = -6x + 9

subtract 9 from both sides

-6x = -6x

simplify

0 = 0

User Santuxus
by
5.4k points
4 votes

Answer: The answer for this question is x=1

Step-by-step explanation: -3(2x-3)=-6x+9 first you multiply -3x with 2x and -3 to get -6x+9=-6x+9 then subtract nine from both sides to leaves -6x=-6x then you divide -6 on both sides and you get x=1.

User Matoe
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.